Realistic fatigue damage assessment of a high-speed train bogie frame by damage consistency load spectra based on measured field load. (15th December 2020) - Ji, Chengxiang; Sun, Shouguang; Li, Qiang; Ren, Zunsong; Yang, Guangxue
Highlights: Field load histories acting on a high-speed train bogie frame were measured. Load-strain response matrix was obtained for load spectra damage calculation. Damage consistency load spectra were established by a novel calibration method. Damage consistency load spectra perform a higher fatigue assessment accuracy. Abstract: This work focused on the realistic fatigue damage assessment of a high-speed train bogie frame under actual service conditions. The bogie frame and its attached components were strain gauged and statically calibrated to measure field load histories. The stress histories and load–strain response matrix at the fatigue key points (FKPs) were obtained for calculation of the actual and load spectra damage, respectively. According to the damage consistency criterion, the damage consistency load spectra (DCLS) were established based on the measured field load by a novel calibration method. This method was based on that the damage percentage of each load series at the FKPs can produce a more reasonable set of calibration coefficients, and the DCLS established by this method has a higher fatigue assessment accuracy. The damage ratios indicated that the DCLS yielded a more realistic fatigue damage assessment than the fatigue test spectrum specified in the relevant standards.